2020
DOI: 10.1021/acs.orglett.0c02049
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Temperature Dependence of Kinetic Isotope Effects in Hydride-Transfer Reactions of NADH/NAD+ Analogues in Solution: Reaction Center Rigidity Is the Key

Abstract: Substituent effects on the temperature dependence of primary kinetic isotope effects, characterized by ΔE a = E aD − E aH , for two series of the title reactions in acetonitrile were studied. The change from ΔE a ≈ 0 for a highly rigid system to ΔE a > 0 for systems with reduced rigidities was observed. The rigidities were controlled by the electronic and steric effects. This work replicates the observations in enzymes and opens a new research direction that studies structure−ΔE a relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(48 citation statements)
references
References 44 publications
(80 reference statements)
7
41
0
Order By: Relevance
“…While these 1° KIE observations in enzymes appear to be well explained by the new VA-AHT model, further systematic studies of the DAD TRS – Δ E a relationship for general H-transfer reactions are needed to test the explanations and the model. As a matter of fact, we have studied the structure – Δ E a relationship for several hydride transfer reactions in solution and concluded that the more rigid reaction centers with more densely distributed DAD TRS ’s gave rise to a smaller Δ E a value, supporting the predicted DAD TRS – Δ E a relationship in the model and explanations for the observations in enzymes. , It should be noted, however, that the other contemporary H-tunneling model or other methods of simulation of H-tunneling have also been attempted to explain the above KIE observations in enzymes, and sometimes similar DAD TRS explanations were resulted, but only the VA-AHT model is able to predict such a relationship beforehand. , …”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…While these 1° KIE observations in enzymes appear to be well explained by the new VA-AHT model, further systematic studies of the DAD TRS – Δ E a relationship for general H-transfer reactions are needed to test the explanations and the model. As a matter of fact, we have studied the structure – Δ E a relationship for several hydride transfer reactions in solution and concluded that the more rigid reaction centers with more densely distributed DAD TRS ’s gave rise to a smaller Δ E a value, supporting the predicted DAD TRS – Δ E a relationship in the model and explanations for the observations in enzymes. , It should be noted, however, that the other contemporary H-tunneling model or other methods of simulation of H-tunneling have also been attempted to explain the above KIE observations in enzymes, and sometimes similar DAD TRS explanations were resulted, but only the VA-AHT model is able to predict such a relationship beforehand. , …”
Section: Introductionmentioning
confidence: 58%
“…In others, secondary (2°) KIEs on the H/D position at or near the reaction centers have been used as a ruler for the crowdedness at the reaction centers or the tightness of the electronically associated TRS structures providing information for the relative density of of the DAD TRS distributions . Moreover, determination of the stable structures that mimic the PRCs of the enzymatic reactions have been used to provide information about the qualitative order of DAD TRS magnitudes in wild-type enzymes and variants to correlate with the Δ E a ’s. , We have also used similar methods to investigate such correlations for the hydride transfer reactions in solution. , While these have indirectly helped with understanding of the relationship between DAD TRS and Δ E a , a direct correlation between the two would be needed to effectively test the VA-AHT model or to help build future necessary models. To investigate the latter correlation, TRS structures for H-transfer reactions need to be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active center of NADH is 1,4‐dihydropyridine structure (Scheme 1). The common mechanism of NADH as hydride or electron source includes the one‐step hydride transfer mechanismwhen NADH and its analogues react with some negative ions, such as 9‐phenylxanthylium perchlorate (PhXn + ClO 4 − ) [4–8] . In addition to the one‐step hydride transfer mechanism, the other common mechanism is hydrogen atom transfer sequentially with electron transfer mechanism when NADH and its analogues react with some active radicals, such as 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH . )…”
Section: Compound Energy Bnah Heh2 Arch2 H− H H− H H− Hmentioning
confidence: 99%
“…The common mechanism of NADH as hydride or electron source includes the one-step hydride transfer mechanismwhen NADH and its analogues react with some negative ions, such as 9-phenylxanthylium perchlorate (PhXn + ClO 4 À ). [4][5][6][7][8] In addition to the one-step hydride transfer mechanism, the other common mechanism is hydrogen atom transfer sequentially with electron transfer mechanism when NADH and its analogues react with some active radicals, such as 1,1diphenyl-2-picrylhydrazyl (DPPH * ). [9] In previous literatures, [10][11][12][13][14][15][16][17] there are three usual NADH analogues, 1-benzyl-1,4-dihydro nicotinamide (BNAH), Hantzsch (HEH 2 ), N-methyl-9,10-dihydroacridine (AcrH 2 ), which have the same 1,4-dihydropyridine as the active center structure (Scheme 2).…”
mentioning
confidence: 99%